Strategic Leadership for Sustainable Tourism in Indonesia: Transformation, Adaptation, and Inclusion - Atmaja, Hanung Eka; Verawati, Dian Marlina (Jurnal Economic Resource, 2025)
Tourism sustainability is a major challenge in the development of tourist destinations in Indonesia, especially in the midst of climate change, digitalisation, and the growing need for social inclusion. This research aims to explore the role of strategic leadership in driving tourism sustainability through transformation, adaptation and inclusion approaches. This research uses a systematic literature review approach to identify and analyse literature relevant to the topic. By analysing various scholarly articles, research reports, and related publications, this research reveals that the application of these three approaches-transformation, adaptation, and inclusion-can create a holistic strategic framework to achieve tourism sustainability. The findings provide insights into how strategic leadership can enhance the effectiveness of sustainability policies and encourage community engagement in tourism destination management. This research contributes to the tourism leadership and sustainability literature and offers a framework that can be used for further research in managing sustainable tourism in Indonesia.